2006
DOI: 10.1016/j.cellbi.2006.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chilling on male gametophyte development in rice

Abstract: Chilling during male gametophyte development in rice inhibits development of microspores, causing male sterility. Changes in cellular ultrastructure that have been exposed to mild chilling include microspores with poor pollen wall formation, abnormal vacuolation and hypertrophy of the tapetum and unusual starch accumulation in the plastids of the endothecium in post-meiotic anthers. Anthers observed during tetrad release also have callose (1,3-beta-glucan) wall abnormalities as shown by immunocytochemical labe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
116
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(134 citation statements)
references
References 41 publications
8
116
0
5
Order By: Relevance
“…On the other hand, microarray analysis of rice anthers showed that the expression of an invertase and two sucrose synthase genes was down-regulated by chilling (Yamaguchi et al 2004). It has also been reported that the expression of OsINV4 and OsMST8 (anther-specific genes) decreased in rice exposed to low temperatures, and that the decrease in the expression of OsINV4 and OsMST8 during chilling was associated with poor pollen wall formation, abnormal vacuolation and hypertrophy of the tapetum, and unusual starch accumulation in post-meiotic anthers (Mamun et al 2006, Oliver et al 2005, 2007. Thus, the changes in expression of OsSUT1, OsSUT2 and OsSUT4 accompanied by other genes related to sugar transport (Lemoine et al 2013) should cause the repression in sugar supply to the anther/pollen via long-and short-distance sucrose transport from source tissues during chilling.…”
Section: Relationship Between Cold Tolerance and Transport Of Sugars mentioning
confidence: 95%
“…On the other hand, microarray analysis of rice anthers showed that the expression of an invertase and two sucrose synthase genes was down-regulated by chilling (Yamaguchi et al 2004). It has also been reported that the expression of OsINV4 and OsMST8 (anther-specific genes) decreased in rice exposed to low temperatures, and that the decrease in the expression of OsINV4 and OsMST8 during chilling was associated with poor pollen wall formation, abnormal vacuolation and hypertrophy of the tapetum, and unusual starch accumulation in post-meiotic anthers (Mamun et al 2006, Oliver et al 2005, 2007. Thus, the changes in expression of OsSUT1, OsSUT2 and OsSUT4 accompanied by other genes related to sugar transport (Lemoine et al 2013) should cause the repression in sugar supply to the anther/pollen via long-and short-distance sucrose transport from source tissues during chilling.…”
Section: Relationship Between Cold Tolerance and Transport Of Sugars mentioning
confidence: 95%
“…Special mention must be given to the work done in rice (Oryza sativa L.), initiated in the 1970s by Japanese researchers (Nishiyama, 1984;Satake and Hayase, 1970) and later confirmed by many authors (e.g. Jagadish et al, 2007;Mamun et al, 2006;Prasad et al, 2006), relating chilling and heat stress during booting (early gametophyte development) and flowering to higher spikelet sterility. Similarly, the effect of high temperatures during flowering in tomato (Solanum lycopersicum L.) has also been studied in detail, and not only extreme high temperatures, but even a mild increase in temperature during a short spell coincident with some flowering stages have been shown to affect negatively fruit set Page 6 of 24 A c c e p t e d M a n u s c r i p t 6 (Abdulbaki and Stommel, 1995;Sato et al, 2002).…”
Section: Page 5 Of 24mentioning
confidence: 99%
“…Meiosis has been recurrently reported as a highly sensitive stage to temperature in many species (Ahmed et al, 1992;Clarke and Siddique, 2004;Erickson and Markhart, 2002;Prasad et al, 2003), although the precise mechanism underlying this sensitivity is still not well known. Premature dissolution of the callose wall that surrounds dividing microspores (late meiosis) and the subsequent poor wall development in the resultant microspores has been interpreted as the main reason for pollen sterility in rice under cold stress (Mamun et al, 2006). Early microspore development was reported to be also highly sensitive to chilling stress in the same species (Mamun et al, 2006).…”
Section: Male Development: Pollen Development and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive heat perturbs many cellular and developmental processes and directly affects grain production by reducing fertility and grain quality (Barnabás et al, 2008). Male gametophyte development is the facet of reproduction that appears most prone to disruption by drought, heat, and cold stresses (Saini, 1997;Mamun et al, 2006). However, it is unclear at present whether there is any common basis to the sensitivity of male reproduction to the various stresses.…”
Section: Qtls For Low-and High-temperature Tolerancementioning
confidence: 99%